Những câu hỏi liên quan
Kiên Đỗ
Xem chi tiết
nguyenvandoanh
Xem chi tiết
Nguyễn Lê Phước Thịnh
14 tháng 10 2022 lúc 14:55

\(=\left(sin^2a+cos^2a\right)^3-3sin^2a\cdot cos^2a\cdot\left(sin^2a+cos^2a\right)+3sin^2a\cdot cos^2a\)

=1

Bình luận (0)
Vui Nguyen
Xem chi tiết
Ngọc Hạnh Nguyễn
Xem chi tiết
Trần Đức Thắng
Xem chi tiết
Trần Thị Loan
15 tháng 7 2015 lúc 22:19

A = (sin2a + cos2a)3 - 3sin2a. cos2a.(sin2a + cos2a) + 3sin2a.cos2a = 1 - 3sin2a. cos2a + 3sin2a. cos2a = 1

Bình luận (0)
tran duc huy
Xem chi tiết
Nguyễn Việt Lâm
28 tháng 11 2019 lúc 0:01

\(\frac{cosa}{1+sina}+\frac{sina}{cosa}=\frac{cos^2a+sina\left(1+sina\right)}{cosa\left(1+sina\right)}=\frac{1+sina}{cosa\left(1+sina\right)}=\frac{1}{cosa}\)

\(\frac{sin^2a+cos^2a+2sina.cosa}{\left(sina-cosa\right)\left(sina+cosa\right)}=\frac{\left(sina+cosa\right)^2}{\left(sina-cosa\right)\left(sina+cosa\right)}=\frac{sina+cosa}{sina-cosa}=\frac{\frac{sina}{cosa}+1}{\frac{sina}{cosa}-1}=\frac{tana+1}{tana-1}\)

\(\left(sin^2a\right)^3+\left(cos^2a\right)^3=\left(sin^2a+cos^2a\right)^3-3sin^2a.cos^2a\left(sin^2a+cos^2a\right)\)

\(=1-3sin^2a.cos^2a\)

\(sin^2a-tan^2a=tan^4a\left(\frac{sin^2a}{tan^4a}-\frac{1}{tan^2a}\right)=tan^4a\left(sin^2a.\frac{cos^2a}{sin^2a}-\frac{1}{tan^2a}\right)\)

\(=tan^4a\left(cos^2a-cot^2a\right)\) bạn ghi sai đề câu này

\(\frac{tan^3a}{sin^2a}-\frac{1}{sina.cosa}+\frac{cot^3a}{cos^2a}=tan^3a\left(1+cot^2a\right)-\frac{1}{sina.cosa}+cot^3a\left(1+tan^2a\right)\)

\(=tan^3a+tana-\frac{1}{sina.cosa}+cot^3a+cota\)

\(=tan^3a+cot^3a+\frac{sina}{cosa}+\frac{cosa}{sina}-\frac{1}{sina.cosa}\)

\(=tan^3a+cot^3a+\frac{sin^2a+cos^2a-1}{sina.cosa}=tan^3a+cot^3a\)

Bình luận (0)
 Khách vãng lai đã xóa
Nguyễn Hoàng Minh Quang
Xem chi tiết
WitherMaster VNTM
Xem chi tiết
Nguyễn Lê Phước Thịnh
9 tháng 10 2022 lúc 11:06

a: \(M=\dfrac{1}{tana+cota}=1:\left(\dfrac{sina}{cosa}+\dfrac{cosa}{sina}\right)\)

\(=1:\dfrac{sin^2a+cos^2a}{cosa\cdot sina}=cosa\cdot sina=\dfrac{2\sqrt{2}}{9}\)

b: \(A=\left(sin^2a+cos^2a\right)^3-3\cdot sin^2a\cdot cos^2a+3\cdot sin^2a\cdot cos^2a\)

=1

Bình luận (0)
phan tuấn anh
Xem chi tiết
Nguyễn Nhật Minh
15 tháng 12 2015 lúc 11:47

\(A=\sin^6x+\cos^6x+3.1.\sin^2x.\cos^2x=\)\(\sin^6x+\cos^6x+3.\left(sin^2x+\cos^2x\right).\sin^2x.\cos^2x=\left(\sin^2x+\cos^2x\right)^3=1^3=1\)

Bình luận (0)